Cryofixation of Inactivated Hantavirus-Infected Cells as a Method for Obtaining High-Quality Ultrastructural Preservation for Electron Microscopic Studies - Parvate, Amar; Sengupta, Ranjan; Williams, Evan P.; Xue, Yi; Chu, Yong-Kyu; Stahelin, Robert V.; Jonsson, Colleen B. (Frontiers in Cellular and Infection Microbiology, 2020)
Hantaviruses rewire the host cell and induce extensive membrane rearrangements for their replication and the morphogenesis of the virion. Transmission electron microscopy (TEM) is a powerful technique for imaging these pathological membrane changes especially when combined with large volume electron tomography. Excellent preservation of membrane structure can be obtained when chemical fixation is combined with cryofixation via high pressure freezing making the samples amenable to serial-section tomographic reconstruction. Taking advantage of this, we have optimized a hybrid method that employs aldehyde fixation, a step that is essential for virus inactivation, followed by high-pressure freezing for ultrastructural study of Hantaan (HTN) and Andes (AND) virus infected Vero E6 cells. HTNV and ANDV are two species of the Orthohantavirus, from the Old and New World, respectively, and the causative agents of hemorrhagic fever with renal syndrome and hantavirus pulmonary syndrome in humans. We applied the method for the qualitative assessment of the perturbation of the endomembrane system induced by HTNV and ANDV in infected versus mock-infected cells. Screening of serial-sections revealed consistency of membrane preservation across large volumes indicating potential of these samples for tomographic studies. Images revealed large-scale perturbations of the endomembrane system following HTNV-infection that included the dilation of the rough endoplasmic reticulum and fragmentation of the Golgi apparatus. Infected cells exhibited a tendency to accumulate large numbers of vacuoles that were especially apparent in ANDV. In summary, our hybrid method provides a path for the study of BSL-3 pathogens using cutting edge 3D-imaging technologies.